The Crisis of Palestinian Non-Governmental Organizations within the context of Rehabilitating Civil Society in ‎Palestine - Sheta‎, Mustafa Helal; Yousef, Ayman Talal (Dirasat: Human and Social Sciences, 2025)
Objectives: This research seeks to explore the structural crisis facing Palestinian civil society, with a special focus on Palestinian non-governmental organizations. It examines the crises they face, such as those related to conditional funding provided by donors, and Palestinian Authority policies towards civil society. Methods: The study combines a qualitative research design with a case study approach, as the case study effectively provides a detailed and in-depth analysis of a phenomenon in its general context, including empirical considerations. This new approach takes advantage of secondary sources and literature, including academic sources in the form of books, magazines, periodicals, and reports. Results: The importance of examining the crisis of non-governmental organizations lies in the decisive role they play in promoting democracy and human rights, and in achieving social justice, given that these civil organizations are a major player in the processes of development, democratic transformation, and political and social change. Conclusions: NGOs are vital nowadays in all societies, including the Palestinian society under occupation, particularly NGOs involved in the processes of democratization, resilience and development.